The STP Marketing Strategy of Toyota Agya and the Influence of Brand Image on Consumer Purchase Decisions in Jambi City - Jamira, Anaseputri; Asmas, Denny; Amali, Muhammad (Dinasti Publisher, 2025)
Brand image plays a significant role in influencing consumer purchasing decisions. This study aims to describe the relationship between brand image, purchasing decisions, and the STP (Segmentation, Targeting, and Positioning) marketing strategy of Toyota Agya in Jambi City. This study uses a quantitative descriptive method, with data analyzed using SPSS through a simple linear regression model. The results show that brand image has a significant positive effect on consumer purchasing decisions in Jambi City. Furthermore, based on the STP analysis, segmentation focuses on urban middle-income consumers seeking affordable, fuel-efficient, and compact vehicles. The targeting strategy emphasizes young professionals, small families, and first-time car buyers who value practicality and cost efficiency. Meanwhile, the positioning strategy presents the product as an economical city car that offers reliability, safety, and a modern design supported by a strong brand reputation. Overall, the results of the study indicate that an effective STP marketing strategy, combined with a strong brand image, significantly influences consumer purchasing decisions.